The effect of two different high-flux dialysis membranes on insulin resistance in non-diabetic end-stage renal disease patients. (14th September 2015) - Kara, Mujdat; Gurluler, Ercument; Cakır, Ulkem
Abstract: Objective : The aim of this study was to investigate the effect of two different types of high-flux dialysis membranes on insulin resistance among patients who are receiving hemodialysis (HD) due to end-stage renal failure (ESRF). Materials and methods : Forty-six (21 female, 25 male) patients were included in the study, who were on HD treatment due to stage-5 chronic renal failure. Prior to the study, fasting insulin resistance via Homeostasis Model Assessment-Insulin Resistance (HOMA-IR) and fractioned urea clearance ( Kt / V ) values were calculated using the urokinetic model. The polysulfone (PS) dialysis membrane of all patients included in the study was replaced with "polyarylethersulfone, polyvinylpyrrolidone, polyamide (PPP)" high-flux membrane that has the same surface area over 12 weeks. At the end of the 12-week period, HOMA and Kt / V values were recalculated. Results : At the end of the 12-week period, Kt / V values rose statistically significant from 1.575 to 1.752 ( p = 0.002). HOMA-IR values declined, though not statistically significant, from 3.268 to 2.926 ( p = 0.085). PPP high-flux membrane increased the Kt/V values significantly compared to the PS membrane, while it decreased the insulin resistance and increased insulin sensitivity. Conclusion : The two different types of high-flux dialysis membranes used for HD have different effects on insulin sensitivity. Compared to the PS membrane, PPP high-flux membrane decreased insulin resistance by increasing insulin sensitivity among non-diabetic ESRF patients.